Chronic graft-versus-host disease - the role of dermatological treatment - Magdalena Żychowska; Joanna Gruber-Kopczyńska; Małgorzata Tupikowska-Marzec; Joanna Maj (Termedia Publishing House, 2017)
Introduction . The number of allogeneic haematopoietic stem cell transplantations is increasing year by year. The most common long-term complication is chronic graft-versus-host disease, with skin involvement noted in over 90% of cases. Objective . To present and discuss skin lesions occurring in chronic graft-versus-host disease with a particular focus on available dermatological treatment modalities. Case report . A 45-year-old male patient, who received allogeneic haematopoietic stem cell transplantations in December 2012, presented for the treatment of skin lesions secondary to chronic graft-versus-host disease. Clinical examination revealed hyperpigmented lichenoid eruption on the trunk; irregular patches of non-scarring alopecia; poikiloderma on the face and upper limbs; and sclerodermatous lesions on the hands with diffuse epidermal exfoliation on the palms and soles. Histopathological examination confirmed the diagnosis of chronic graft-versus-host disease. Treatment consisting of phototherapy and intensive topical treatment was introduced. Conclusions . Skin lesions secondary to chronic graft-versus-host disease may impair the daily functioning of post-transplant patients. Comprehensive therapeutic management should be based on the cooperation between haematologists and dermatologists.